Aktuelle Evidenzlage zur Beurteilung der Fahrtauglichkeit von Menschen mit kognitiven Einschränkungen: Ein systematisches Review - Karrer, Linda; Pfleger, Elisabeth; Kolominsky-Rabas, Peter (Gesundheitswesen, 2022)
Zusammenfassung Einleitung Aufgrund der hohen Prävalenz demenzieller Erkrankungen handelt es sich bei der Überprüfung der Fahrtauglichkeit von Menschen mit kognitiven Beeinträchtigungen um ein Thema von großer gesellschaftlicher Relevanz. Methodik Es wurde eine umfassende systematische Literaturrecherche zu der Forschungsfrage: „Welche evidenz-basierten Methoden eignen sich zur Beurteilung der Fahrtauglichkeit von Menschen mit Demenz (MmD) oder milden kognitiven Einschränkungen (MCI)?“ für den Zeitraum 2015–2020 durchgeführt. Die Recherche erfolgte in den Datenbanken Medline, PsycINFO, LIVIVO, PubPsych, Scopus, Cinahl und CENTRAL. Ergebnisse 30 Studien wurden in die qualitative Analyse eingeschlossen. Die Fahrtauglichkeit kann mit praxisbasierten Testverfahren wie Praxisfahrtest (On-road), Fahrsimulator und Fahrverhaltensbeurteilung im natürlichen Umfeld (Naturalistic Driving) beurteilt werden. Theoriebasierte Methoden sind: neuropsychologische Tests, fahrspezifische Testungen und Fragebögen zur Selbsteinschätzung. Die Studienlage zeigt, dass einzelne neuropsychologische Tests nicht zur Bestimmung der Fahrtauglichkeit ausreichen. Eine höhere Aussagekraft haben praxisbasierte Testverfahren, fahrspezifische Testungen sowie Kombinationen aus evidenz-basierten Methoden. Schlussfolgerungen Die Überprüfung der Fahrtauglichkeit von Menschen mit kognitiven Beeinträchtigungen sollte angesichts des progredienten Verlaufs demenzieller Erkrankungen engmaschig durch eine Kombination aus theorie- und praxisbasierter Methoden erfolgen.<br

Digital Dementia Registry Bavaria - DigiDEM Bayern: Study protocol for a multicentre, prospective, longitudinal register study - Dietzel, Nikolas; Kürten, Lara; Karrer, Linda; Reichold, Michael; Köhler, Laura; Nagel, Andreas; Chmelirsch, Christina; Seebahn, Kathrin; Hladik, Markus; Meuer, Sebastian; Kirchner, Anna; Holm, Kristina; et al. (BMJ Open, 2021)
Introduction Dementia is one of the most relevant widespread diseases, with a prevalence of currently 50 million people with dementia worldwide. The care of people with dementia will be one of the major challenges for healthcare systems worldwide. Digitalisation offers new possibilities to improve both dementia healthcare and health outcomes research as a fundament for national healthcare planning. The a € Digital Dementia Registry Bavaria - digiDEM Bayern' aims to improve the understanding of the complexity and long-term progression of dementia and the current care situation in Bavaria. Moreover, by offering digital services, digiDEM will actively contribute to improving the care situation in Bavaria. Methods and analysis digiDEM will recruit people with dementia and their family caregivers in all administrative regions of Bavaria. All participants will undergo dementia screening prior to study inclusion in order to identify people with mild cognitive impairment and mild-to-moderate dementia. Participants will be followed up over a period of three years. Sociodemographic data, type of dementia, symptoms, diagnosis, cognitive trajectories, activities of daily living, behavioural and psychological symptoms, falls, resource utilisation, caregiver burden, quality of life, needs of people with dementia and their caregivers, mobility, use of media and sources of information will be assessed. The project will implement a digital web-based platform for data collection. Data will be collected by means of standardised online or face-to-face interviews. Ethics and dissemination The study obtained ethical approval from the Ethics Committee of the Medical Faculty of Friedrich-Alexander-University Erlangen-Nürnberg (FAU) (application number: 253_20 B). Findings will be used for evidence-based decision-making for health decision-makers in order to optimise dementia healthcare in the state of Bavaria. Specific analyses will be conducted for the participating research partners. Results of the study will be published in peer-reviewed journals.
CRIS-Team Scopus Importer:2021-02-26
Keywords: dementia; neurology; public health

Einflussfaktoren auf die Pflegebelastung der Angehörigen von Menschen mit Demenz: der Bayerische Demenz Survey (BayDem) - Dietzel, Nikolas; Karrer, Linda; Wolff, Franziska; Kratzer, André; Hess, Manuela; Grässel, Elmar; Kolominsky-Rabas, Peter (Gesundheitswesen, 2020)
Background Dementia is an age-specific disease with increasing care needs over the course of the disease. Care is predominantly conducted by caregivers. Caregiver burden is a core criterion for the evaluation of the care situation. The aims of this examination are to identify predictors of caregiver burden and to analyze the course of the caregiver burden over a 12 months period. Methods The Bavarian Dementia Survey (BayDem) is a supra-regional, longitudinal study carried out at 3 different sites in Bavaria, Germany. Participants were people with dementia (pwd) as defined by ICD-10 and their informal caregivers. Data was collected by standardized face-to-face interviews in cooperation with local actors. For statistical analysis, a multiple regression as well as a mixed ANOVA (Analysis of Variance) and repeated measures ANOVAs were used. Results In this analysis, 295 pwd and 276 caregivers were studied. Key factors influencing caregiver burden were gender of the pwd, behavioral and psychological symptoms and a decline of everyday functioning of the pwd as well as gender of the informal caregivers, their relation to the pwd and if they live at the same household as the pwd. Analysis showed a significant main effect of time over the course of the caregiver burden. Conclusion A permanent high caregiver burden can cause health problems for the caregivers. However, caregivers can be supported according to the specific factors of the caregiver burden. One approach in order to support caregivers could be a combination of pharmacological and non-pharmacological interventions for the treatment of disease-specific symptoms and an empowerment as well as the provision of support services for the caregivers. Furthermore, tailored services for specific target groups can be meaningful.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Burden Scale for Family Caregivers (BSFC-s); caregiver burden; course; dementia; informal caregivers; predictors

Exploring physicians and patients' perspectives for current interventions on thyroid nodules using a MCDA method - Karrer, Linda; Zhang, Shixuan; Kühlein, Thomas; Kolominsky-Rabas, Peter (Cost Effectiveness and Resource Allocation, 2021)
Background The detection of thyroid cancer has rapidly increased over last few decades without an increase in disease specific mortality. Several studies claim that the diagnose of thyroid nodules through routine ultrasound imaging is often the trigger for cascade effects leading to unnecessary follow-up over many years or to invasive treatment. The objective of this study was to explore physicians' and patients' insights and preferences regarding the current interventions on thyroid nodules. Methods An online survey was developed using a comprehensive multi-criteria decision analysis (MCDA) framework, the EVIdence based Decision-Making (EVIDEM). The EVIDEM core model used in this study encompassed 13 quantitative criteria and four qualitative criteria. Participants were asked to provide weights referring to what matters most important in general for each criterion, performance scores for appraising the interventions on thyroid nodules and their consideration of impact of contextual criteria. Normalized weights and standardized scores were combined to calculate a value contribution across all participants, additionally differences across physicians and patients' group were explored. Results 48 patients and 31 physicians were included in the analysis. The value estimate of the interventions on thyroid nodules reached 0.549 for patients' group and 0.5 was reported by the physicians' group, compared to 0.543 for all participants. The highest value contributor was 'Comparative effectiveness' (0.073 +/- 0.020). For the physicians' group, 'Comparative safety' (0.050 +/- 0.023) was given with higher value. And for the patients' group, 'Type of preventive benefits' (0.059 +/- 0.022) contributed more positively to the value estimation. 51% participants considered 'Population priorities and access' having a negative impact on the interventions of nodules.66% participants thought that the 'system capacity' had a negative impact. Conclusion Our study shows participants' preferences on each criterion, i.e., physician indicated keeping the interventions safe and effective more important, patients indicated quality of life after receiving interventions more important. Through comparison among participants, differences have been highlighted, which can make better communication between physicians and patients. This study provides a supportive decision-making for healthcare providers when they explored the interventions on thyroid nodules.
CRIS-Team WoS Importer:2021-05-21

Stakeholder perspectives on the key components of a digital service platform supporting dementia - Digidem Bayern - Reichold, Michael; Dietzel, Nikolas; Karrer, Linda; Grässel, Elmar; Kolominsky-Rabas, Peter; Prokosch, Hans-Ulrich (Studies in Health Technology and Informatics, 2020)
The increasing number of people with dementia and caregiving relatives will require a change in the provision of dementia-related services in the future. Digital technologies are a force for change. The new project digiDEM Bayern with its digital services on a digital platform and a digital patient registry should help to improve the situation for people with dementia and their caregivers especially in rural settings. An online survey among service providers for people with dementia and caregiving relatives in Bavaria was conducted to find out how they assess the current landscape of digital and non-digital service offers for people with dementia and their caregivers. The results of the survey have revealed that there is currently a large gap in the provision of digital services varying between the different categories surveyed. digiDEM Bayern addresses this gap with its digital dementia-related service platform.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Dementia; Digital; Informal caregiver; Platform; Services; Stakeholder

Symptombelastung, Inanspruchnahme des Gesundheitssystems und Todesumstände von Menschen mit Demenz in der letzten Lebensphase: der Bayerische Demenz Survey (BayDem) - Kratzer, André; Karrer, Linda; Dietzel, Nikolas; Wolff, Franziska; Hess, Manuela; Kolominsky-Rabas, Peter; Grässel, Elmar (Gesundheitswesen, 2020)
Background Dementia is usually a life-limiting disease. However, evidence-based guidelines for palliative care for people with dementia (PwD) are currently lacking. One reason for this is the dearth of reliable empirical data on PwD at the end of life. The aim of this study is to describe the symptom burden, causes of death, places of death and the use of various health services for PwD at the end of life. Methods The Bavarian Dementia Survey (BayDem) was a multi-center, longitudinal study at 3 different sites in Bavaria, Germany (Dachau, Kronach, Erlangen). Participants were PwD defined by ICD-10 and their informal caregivers. Data were collected in standardized face-to-face interviews in cooperation with local actors. In order to obtain comparable groups, deceased and non-deceased PwD were matched using 1:1 propensity score matching. For the statistical analyses, McNemar tests as well as paired t-tests were used. Results In this analysis, 58 deceased and 58 non-deceased PwD were studied (n=116). In most cases, PwD died at home (36.2%), in hospital (25.9%) or in a nursing home (19.0%), but no one in palliative care. The most common causes of death were respiratory (13.8%) and cardiovascular complications (12.1%) as well as stroke (12.1%). PwD at the end of life showed more pronounced physical comorbidities than the other PwD (Charlson-Index: M=2.75 vs. M=1.80; p=0.030, Cohen's d=0.425) and were therefore admitted to hospital (46.6 vs. 12.1%, p<0.001, OR=6.250) or emergency departments (22.4 vs. 3.4%, p=0.007, OR=6.500) more frequently. Behavioral and psychological symptoms were very pronounced (NPI Score: M=31.67 vs. M=24.77, p=0.118, Cohen's d=0.303). Nevertheless, the utilization of outpatient health services was low. Conclusion The results underline the need to develop evidence-based guidelines to provide palliative care specifically adapted to the needs of PwD at the end of life. In this context, the high incidence of behavioral and psychological symptoms should be taken into account, as should the high incidence of physical comorbidities. Considering the frequent hospital admissions, special attention should also be paid to the development of recommendations for the inpatient sector (acute hospital and palliative care unit).
CRIS-Team Scopus Importer:2020-02-04
Keywords: Death; Dementia; End of life; Palliative care; Symtom burden; Utilization

Wenn es nicht mehr alleine geht – Inanspruchnahme ambulanter Unterstützungsangebote von Menschen mit Demenz: der Bayerische Demenz Survey (BayDem) - Karrer, Linda; Dietzel, Nikolas; Wolff, Franziska; Kratzer, André; Hess, Manuela; Grässel, Elmar; Kolominsky-Rabas, Peter (Gesundheitswesen, 2020)
Background The increasing prevalence of dementia raises challenges concerning the care of people with dementia (pwd). The care of pwd is mainly conducted by informal caregivers who are faced with several burdens; however, use of care services is generally low. The aim of this study was to identify predictors of the use of outpatient care services. Methods The Bavarian Dementia Survey (BayDem) is a multi-centre, longitudinal study that was conducted at 3 different sites in Bavaria, Germany. Participants were people with dementia (pwd) (according to ICD-10) and their informal caregivers. Data were collected by standardised face-to-face interviews using well-designed instruments in cooperation with local partners. Logistic regression analysis was carried out in order to identify predictors of the use of outpatient care services. Results In total, 364 pwd and 339 informal caregivers were included at the beginning of the study BayDem. The use of supportive care services was generally low. One-third of all participants used outpatient care services. In the logistic regression analysis, the following significant predictors for the use of outpatient care services 6 months after baseline were identified: severity of cognitive impairment of the pwd; use of outpatient care at the beginning of the study. Conclusion The low use of outpatient care services is a well-known paradoxical phenomenon. Such services can help give relief to informal caregivers. In order to enhance the use of supportive outpatient care services, there should be more focus on innovative health service delivery models with a low access threshold barrier. Besides more public campaigns, more guidance for existing offers is needed.
CRIS-Team Scopus Importer:2020-02-04
Keywords: informal caregivers; outpatient care; People with dementia; Resource Utilization in Dementia (RUD); use of care services

Zeitgerechte Diagnosestellung bei Menschen mit Demenz: der Bayerische Demenz Survey (BayDem) - Wolff, Franziska; Dietzel, Nikolas; Karrer, Linda; Kratzer, André; Hess, Manuela; Grässel, Elmar; Kolominsky-Rabas, Peter (Gesundheitswesen, 2020)
Background In many cases, people with dementia (PWD) receive their first diagnosis at an advanced stage of the disease. A timely diagnosis, however, is crucial for the utilization of therapies and support services for PWD and their caregivers. So far, only a few international studies have analysed predictors of the time lapse between the first perceived symptoms and diagnosis. The aim of this study was to assess the time span from the first symptoms of dementia until the first dementia diagnosis and to identify predictors of a timely diagnosis. Methods The Bavarian Dementia Survey (BayDem) is a multi-centre, longitudinal study at 3 different sites in Bavaria, Germany. Participants were PWD as defined by ICD-10 and their informal caregivers. Data was collected by standardized face-to-face interviews in cooperation with local actors. For the analysis of potential sociodemographic predictors of a timely diagnosis within 9 months after the perception of the first symptoms, binary logistic regressions were used. Results The median length from the perception of the first symptoms until diagnosis was 16 months. Predictors of a timely diagnosis for male PWD were age at the time of the first perceived symptoms and education. There was no association between a timely diagnosis and the place of residence or living situation of the PWD. Conclusions Diagnosis of dementia is often made with a huge delay. Therefore, it is necessary to enhance structured access routes to a timely diagnosis in primary care.
CRIS-Team Scopus Importer:2020-02-04
Keywords: dementia; diagnostic delay; time to diagnosis; timely diagnosis